How Does Accountability Exacerbate Job Burnout in the Public Sector? Exploratory Research in Production Supervision in China - Zhiyi Fang; Qilin Zhang (Behavioral Sciences)
With the advancement of behavioral public administration, the methodological innovation it introduces offers robust support for investigating the relationship between accountability and individuals’ behavior in the public sector. This paper investigates the link between individuals’ felt accountability and job burnout within China’s industrial production context. We develop and validate a novel theoretical model grounded in cognitive stress theory using survey data collected from public sector safety supervision regulators. The results indicate that the regulators’ felt accountability significantly impacts their job burnout, while threat appraisal played a mediating role in this relationship. Public service motivation negatively moderates the effect, with a more substantial effect observed at higher levels of motivation. This paper contributes to the development of felt accountability theory and promotes interdisciplinary dialogue.